The Perna Women: Vulnerabilities, Opportunities and Work. Issue 2 (December 2018) - Kakoty, Juanita; Mishra, Khushboo; Mir, Anahita
This article has been put together as evidence of the socio-economic existence and vulnerabilities of the Perna community in Dharampura (Najafgarh, Delhi) where prostitution gets translated as the only source of livelihood, as the only opportunity to earn for the entire community. The article also captures the gender-based violence that plays out in this freed/denotified tribe (DNT) community, which becomes more acute while addressing the lives of their women and girls. It is based on field observations and interviews conducted with the women and girls from the Perna community in the Dharampura neighbourhood of Najafgarh during 2015–2018, and raises questions about the state's responsibilities towards such DNT communities.